PENINGKATAN PENGETAHUAN HIV /AIDS PADA KARYAWAN PERKANTORAN SEBAGAI UPAYA PENANGANAN HIV/AIDS PADA USIA PRODUKTIF - Yudha, Raden Rama Widya Kartika; Isnugroho, Hernawan; Sulistyowati, Endang Tri (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2023)
Abstract: HIV/AIDS has become an epidemic throughout the world, including in Indonesia, including office workers. The increase in cases of transmission every year and the absence of proper education are of particular concern. Efforts to prevent the spread of HIV/AIDS can be done by increasing the understanding of people of productive age. Efforts to prevent transmission and eliminate stigma based on education for office employees can be carried out as an effort to increase public awareness of HIV and prevention of transmission, as well as its handling. Education is carried out by presentation and question and answer methods using the media